Asma’ul Husna: Spirit Karakter Religius Gen-Z di Era Kekinian - Angga Hidayat; Abdul Aziz; Masripani , Masripani (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to assess the impact of routine Asma’ul Husna recitation in developing religious character among grade X-3 students at SMAN 3 Palangka Raya. Through a service-learning approach, students are encouraged to understand and internalize the noble values represented by Allah’s 99 names, such as compassion, justice, and wisdom, and to apply these values in their daily lives. The character-building process involves three main stages: routine recitation of Asma’ul Husna, material presentation to understand the meaning of each name, and assignments to practice these values. The findings indicate that this method successfully enhances students' spiritual understanding and fosters positive Islamic character traits, including empathy, discipline, and responsibility. This practice proves to be an effective strategy for character education that strengthens students’ morals and ethics within the context of Islamic education.